2022
DOI: 10.3389/fnins.2022.1006594
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and functional characterization of neuropeptides in crinoid echinoderms

Abstract: Neuropeptides are one of the largest and most diverse families of signaling molecules in animals and, accordingly, they regulate many physiological processes and behaviors. Genome and transcriptome sequencing has enabled the identification of genes encoding neuropeptide precursor proteins in species from a growing variety of taxa, including bilaterian and non-bilaterian animals. Of particular interest are deuterostome invertebrates such as the phylum Echinodermata, which occupies a phylogenetic position that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…It has been shown previously that the pentacrinoid nervous system comprises a complex basiepithelial net of serotonergic, GABAergic and peptidergic neurons, concentrated at the level of the tube feet, and a conspicuous entoneural system comprising cholinergic and peptidergic cells [4, 27]. Immunoreactivity for ß-tubulin showed that the post-metamorphic system was highly interconnected, with five bundles of fibers directing from the entoneural aboral nerve centre to a circumoral nerve ring, which was in turn connected to fibers that run in the tube feet (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown previously that the pentacrinoid nervous system comprises a complex basiepithelial net of serotonergic, GABAergic and peptidergic neurons, concentrated at the level of the tube feet, and a conspicuous entoneural system comprising cholinergic and peptidergic cells [4, 27]. Immunoreactivity for ß-tubulin showed that the post-metamorphic system was highly interconnected, with five bundles of fibers directing from the entoneural aboral nerve centre to a circumoral nerve ring, which was in turn connected to fibers that run in the tube feet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown previously that the pentacrinoid nervous system comprises a complex basiepithelial net of serotonergic, GABAergic and peptidergic neurons, concentrated at the level of the tube feet, and a conspicuous entoneural system comprising cholinergic and peptidergic cells [4,27].…”
Section: Development Of the Post-metamorphic Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…RGP and ISL are present not only in starfish (class Asteroidea), but also in other echinoderms such as sea urchins (class Echinoidea) [33], sea cucumbers (class Holothuroidae) [34,35], brittle stars (class Ohiuroidea) [36], and sea lilies (class Crinoidea) [37]. It was revealed that sea cucumber RGP induces gamete shedding in Holothuria scabra and H. leucospilota [35].…”
Section: Orthologs Of Rgpmentioning
confidence: 99%
“…A. solaris (Mita, Ikeda, et al., 2015 ; Smith et al., 2019 ), Aphelasterias japonica (Mita & Katayama, 2016 ), Asterias rubens (Lin, Mita, et al., 2017 ; Semmens et al., 2016 ), and Astropecten scoparius (Mita, Osugi, et al., 2021 ), revealing evolutionary conservation of both its structure and function. Relaxin‐type peptide precursors have also been identified in other echinoderms, including ophiuroids (brittle stars), holothurians (sea cucumbers), and crinoids (feather stars) (Aleotti et al., 2022 ; Chieu et al., 2019 ; Suwansa‐Ard et al., 2018 ; Zandawala et al., 2017 ). Furthermore, a relaxin‐type peptide triggers spawning in the sea cucumber Holothuria scabra , showing that the gonadotropic action of relaxin‐type peptides also extends to other echinoderms (Chieu et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%